Sustaining Local Library Advocacy in Today's Political Environment - Peter D. Pearson (The Political Librarian, 2023)
This brief white paper offers practical, succinct advice for navigating local library advocacy efforts through two straits: sustainable operational funding and the library's commitment to intellectual freedom, which is chiefly embodied in its unimpeded ability to develop an integral collection that serves the entire community.